Monograph of Holarrhena antidysenterica (linn.) Wall - Syed Muhammad Ali Shah; Khan Usmanghani; Naveed Akhtar; H.M.Asif; M.Akram; Khalil Ahmed; Ghazala Shaheen; Tahira shamim; Riazur Rehman; Ashfaq Ahmad; Laila Sumreen (International Journal of Phytomedicine, 2010)
Holarrhena Antidysenterica is a very significant herbal drug in Unani system of medicine and Ayurvedic system of medicine. This meticulous herb was used to treat a variety of infectious diseases especially in Staphylococcus aureus, Entamoeba histolytica and Escherichia coli. It is a large tree of 30 to 40 feet in height grows widely on the mountains. A large number of pharmacological studies have been done on the bark and seed of the tree.